The monstrumologist - Yancey, Richard ([The monstrumologist, 2009)
In 1888, twelve-year-old Will Henry chronicles his apprenticeship with Dr. Warthrop, a scientist who hunts and studies real-life monsters, as they discover and attempt to destroy a pod of Anthropophagi.